Bahasa Inggris - Novantiano, Hendrian; Rahman Nurdianto, Arif; Savirani, Rifda (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
A foreign body, especially an organic type, causes eye injuries due to the infectious reactions it may provoke. Therefore, it is crucial to promptly identify and locate the foreign body to facilitate its removal and prevent undesirable complications. This case report highlights the importance of establishing a diagnosis and providing appropriate management for a case of conjunctival foreign body in the palpebral area. This case involved a 50-year-old male patient presenting with complaints of discomfort and pain in the left eye, particularly when closing the eye. The patient reported a history of being struck in the left eye by a rice stalk two days ago. The visual acuity of the right and left eyes was recorded as 6/6, with intraocular pressure of 18 mmHg using a Schiotz tonometer. A fragment of rice stalk was found embedded in the inferior palpebral conjunctiva. In the eyelid eversion examination, there was no foreign body. The foreign body was only visible when the patient gazed to the left while we pulled down the lower eyelid. In conclusion, in this case, foreign body extraction was performed, followed by topical antibiotic therapy and analgesia. The patient was advised to return for a follow-up in one month.